An Analysis Of Discovery Learning In Teaching English At The First Grade In SMA N 1 Bukittinggi - Eriza, Novia; Safitri, Loli; Eliza, Eliza; Pami Putri, Hilma (Yayasan Lembaga Studi Makwa, 2023)
The purpose of the article is to describe the implementation of discovery learning in English language learning at SMAN 1 Bukittinggi. Several problems were found that were not consistent in following the steps of discovery learning. There are even discovery learning steps that are missed in practice, this is due to the limited availability of time for learning. The aim of this research is to analyze how discovery learning is implemented in English language learning in first grade at SMAN 1 Bukittinggi. The research method uses qualitative descriptive research with the research question how to apply discovery learning in English language learning in first grade at SMAN 1 Bukittinggi. The data collection process used interview techniques and checklist observations with informants in the form of students and English teachers at SMAN 1 Bukittinggi. The findings from this research are that teachers have implemented discovery learning in teaching English. such as: stimulation, problem statement, data collection, data processing, verification, and generalization. Although it was still found that several steps were not consistently implemented by teachers in several meetings. However, this does not affect the implementation of discovery learning steps in English at SMAN 1 Bukittinggi. Teachers should guide students to identify historical recounts and create temporary hypotheses. Meanwhile, researchers found that teachers directly directed students to look for information regarding the historical recount. The conclusion is that by implementing discovery learning used by teachers, they are able to increase good grades and students become active in the learning process. Abstrak Tujuan dari artikel untuk mendeskripsikan implementasi dari discovery learning dalam pembelajaran bahasa inggris di SMAN 1 Bukittinggi. Beberapa persoalan ditemukan bahwa belum konsisten dalam mengikuti langkah dari discovery learning. Bahkan ada langkah discovery learning yang terlewatkan dalam prakteknya, ini disebabkan ketersediaan waktu yang terbatas dalam pembelajaran. Tujuan dari penelitian ini untuk menganalisis bagaimana pengimplementasian discovery learning dalam pembelajaran bahasa inggis di kelas satu di SMAN 1 Bukittinggi. Metode penelitian yang gunakan deskriptif kualitatif dengan pertanyaan penelitian bagaimana penerapan discovery learning dalam pembelajaran bahasa inggris di kelas satu di SMAN 1 Bukittinggi. Proses pengumpulan data menggunakan teknis wawancara dan observasi checklist dengan informan berupa siswa dan guru bahasa Inggris SMAN 1 Bukittinggi. Temuan dari penelitian ini bahwa guru telah mengimplementasikan discovery learning dalam mengajar bahasa inggris. seperti: stimulation, problem statment, data collection, data processing, verification, and generalization. Meskipun masih ada yang ditemukan beberapa langkah yang kurang konsisten dilaksanakan oleh guru di beberapa pertemuan. Namun hal ini tidak mempengaruhi dalam mengimplementasikan langkah-langkah discovery learning dalam bahasa inggris di SMAN 1 Bukittinggi. Seharusnya guru membimbing siswa untuk mengidenifikasi historycal recount dan membuat hipotesis sementara. Sedangkan peneliti menemukan guru langsung mengarahkan siswa untuk mencari informasi mengenai historycal recount tersebut. Kesimpulan, bahwa dengan pengimpelementasian discovery learning yang digunakan guru mampu meningkatkan nilai yang bagus dan siswa menjadi aktif dalam proses pembelajaran.